\(\dfrac{5}{12}+\dfrac{3}{16}=\dfrac{5\cdot4+3\cdot3}{48}=\dfrac{29}{48}\)
\(\dfrac{4}{15}-\dfrac{2}{9}=\dfrac{4\cdot3-2\cdot5}{45}=\dfrac{2}{45}\)
a) \(\dfrac{5}{12}+\dfrac{3}{16}=\dfrac{20}{48}+\dfrac{9}{48}=\dfrac{29}{48}\)
b) \(\dfrac{4}{15}-\dfrac{2}{9}=\dfrac{12}{45}-\dfrac{10}{45}=\dfrac{2}{45}\)
\(a,\dfrac{5}{12}+\dfrac{3}{16}=\dfrac{20}{48}+\dfrac{9}{48}=\dfrac{29}{48}\)
\(b,\dfrac{4}{15}-\dfrac{2}{9}=\dfrac{12}{45}-\dfrac{10}{45}=\dfrac{12-10}{45}=\dfrac{2}{45}\)
a) \(\dfrac{5}{12}+\dfrac{3}{16}=\dfrac{20}{48}+\dfrac{9}{48}=\dfrac{29}{48}\)
b) \(\dfrac{4}{15}-\dfrac{2}{9}=\dfrac{12}{45}-\dfrac{10}{45}=\dfrac{2}{45}\)
a)= \(\dfrac{80}{192}+\dfrac{16}{192}\)
\(=\dfrac{96}{192}\)
=\(\dfrac{1}{2}\)
b)=\(\dfrac{36}{135}-\dfrac{30}{135}\)
=\(\dfrac{6}{135}\)
=\(\dfrac{2}{45}\)